Does microfinance provide only an illusion for poverty alleviation? - Saxena, Ankit; Gupta, Ayushi (International Journal of Psychosocial Rehabilitation, 2020)
This papers endeavors to have a constructive appraisal on relevance and importance of microfinance and using the tools to improving the rural sector or poor condition of the economically weaker sections. Microfinance developed the innovative management and business strategy and focus on the fulfilled improve the micro finance services. Microfinance helps to reduce the poverty and it is based on productive employment creation. Its plays the important role for providing the financial services to the rural poor. Microfinance is beneficial for the countries which is not developed other than and rural poor’s are faced so many problem. Microfinance also focused on the improving MDG (Millennium development goals) poverty reduction. Government also promotes the microfinance. The study focused on the microfinance and the poverty of India. Sometimes people see microfinance as the illusion for some poor’s and villages but microfinance always provided the financial services, target the rural poor’s, improve economy and society.